2014
DOI: 10.1007/s15010-014-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

An atypical case of tularemia presented with pseudoptosis

Abstract: We report an unusual case of tularemia involving pseudoptosis associated with deterioration of the lymphatic drainage system extending from the upper eyelid to the preauricular lymph nodes. A 16-week pregnant patient was admitted with an absess on the neck, preauricular lymphadenopathy, and pseudoptosis on the left side. The micro-agglutination test was positive for Francisella tularensis antibody at a titer of 1/200. The absess was surgically drained and oral cefuroxime was given for 6 weeks. Two weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Tularemia during pregnancy may lead to prematurity or fetal loss. However, healthy newborns who were not adversely affected by maternal tularemia have also been reported [26][27][28][29][30] . There is no consensus regarding the treatment of tularemia during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Tularemia during pregnancy may lead to prematurity or fetal loss. However, healthy newborns who were not adversely affected by maternal tularemia have also been reported [26][27][28][29][30] . There is no consensus regarding the treatment of tularemia during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although tularemia in pregnancy has recently been increasingly reported [2][3][4][5], the number of pregnant women among the 393 patients with tularemia reported by Mengeloglu et al was not indicated. Unfortunately, even though it is vital for the pregnant woman and the fetus to receive the optimal medical treatment, there is not enough reported data on this subject.…”
mentioning
confidence: 99%
“…Unfortunately, even though it is vital for the pregnant woman and the fetus to receive the optimal medical treatment, there is not enough reported data on this subject. We have recently published two cases on tularemia during pregnancy [4,5]. The first patient presented with a large abscess on the cervical area and pseudoptosis [4] and the second patient had an acute dacryocystitis with a large abscess [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations